Cattle resistant to tsetse fly - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Over the last five years, a new avenue seems to have opened up to researchers working on the fight against trypanosomiasis: trypanotolerant cattle. Trypanosomiasis is the scientific name for sleeping sickness, which is transmitted by the tsetse fly....